Safety Planning: A Vital Preliminary Step for Professionals Working With Intimate Partner Violence Victims - Melis Sedef Kahraman; Kathryn Bell (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Domestic violence (DV) is defined as a pattern of assaultive and coercive behaviors, including physical, sexual, and psychological attacks, as well as economic coercion, that adults or adolescents use against their intimate partners (Ganley, 1995). Safety planning is a widely used intervention for professionals working with battered women. Safety planning is referred to as a structured procedure for enhancing the safety of women in DV situations that includes the gathering of information, evaluation of the existing situation, decision-making for the type of advocacy and resources needed and the identification of future strategies on how to respond effectively to violence (Campbell, 2001; Davies et al, 1998; Parker & Gielen, 2014). Although it is seen as the first step of helping battered women and trauma informed care in the United States, the safety planning technique is being limitedly used in Turkey only by women shelters. This review will summarize the characteristics of DV situations, explain the theoretical rationale for safety planning, discuss the safety planning process, clarify therapists responsibilities about safety planning and highlight research findings on the effectiveness of safety planning. [JCBPR 2017; 6(3.000): 141-150]